Can ionophobic nanopores enhance the energy storage capacity of electric-double-layer capacitors containing nonaqueous electrolytes?*The authors are saddened by the passing of George Stell but are pleased to contribute this article in his memory. Some years ago, DH gave a talk at a Gordon Conference that contained an approximation that George had demonstrated previously to be in error in one of his publications. Rather than making this point loudly in the discussion, George politely, quietly, and privately pointed this out later. In 2002, DH shared a room with George at a conference in China. This is remembered fondly. (22nd August 2016) - Lian, Cheng; Liu, Honglai; Henderson, Douglas; Wu, Jianzhong
Abstract: The ionophobicity effect of nanoporous electrodes on the capacitance and the energy storage capacity of nonaqueous-electrolyte supercapacitors is studied by means of the classical density functional theory (DFT). It has been hypothesized that ionophobic nanopores may create obstacles in charging, but they store energy much more efficiently than ionophilic pores. In this study, we find that, for both ionic liquids and organic electrolytes, an ionophobic pore exhibits a charging behavior different from that of an ionophilic pore, and that the capacitance–voltage curve changes from a bell shape to a two-hump camel shape when the pore ionophobicity increases. For electric-double-layer capacitors containing organic electrolytes, an increase in the ionophobicity of the nanopores leads to a higher capacity for energy storage. Without taking into account the effects of background screening, the DFT predicts that an ionophobic pore containing an ionic liquid does not enhance the supercapacitor performance within the practical voltage ranges. However, by using an effective dielectric constant to account for ion polarizability, the DFT predicts that, like an organic electrolyte, an ionophobic pore with an ionic liquid is also able to increase the energy stored when the electrode voltage is beyond a certain value. We find that the critical voltage for an enhanced capacitance in an ionic liquid is larger than that in an organic electrolyte. Our theoretical predictions provide further understanding of how chemical modification of porous electrodes affects the performance of supercapacitors.